Phenotype frequencies of autosomal minor histocompatibility antigens display significant differences among populations. - Eric Spierings; Matthijs Hendriks; Léna Absi; Angelica Canossi; Sonal Chhaya; John Crowley; Harry Dolstra; Jean-François Eliaou; Tom Ellis; Jürgen Enczmann; Maria E Fasano; Thibaut Gervais; et al. (PLoS Genetics)
Minor histocompatibility (H) antigens are allogeneic target molecules having significant roles in alloimmune responses after human leukocyte antigen-matched solid organ and stem cell transplantation (SCT). Minor H antigens are instrumental in the processes of transplant rejection, graft-versus-host disease, and in the curative graft-versus-tumor effect of SCT. The latter characteristic enabled the current application of selected minor H antigens in clinical immunotherapeutic SCT protocols. No information exists on the global phenotypic distribution of the currently identified minor H antigens. Therefore, an estimation of their overall impact in human leukocyte antigen-matched solid organ and SCT in the major ethnic populations is still lacking. For the first time, a worldwide phenotype frequency analysis of ten autosomal minor H antigens was executed by 31 laboratories and comprised 2,685 randomly selected individuals from six major ethnic populations. Significant differences in minor H antigen frequencies were observed between the ethnic populations, some of which appeared to be geographically correlated.